Evaluating farmers' attitudes toward raw wastewater irrigation in Wadi Al- Far'a, Palestine - Al- Qorom, Sameer Moufeed; Abu- Sharar, Taleb Mhmoud; Anayah, Fathi Mohamed; Al- Khatib, Issam Ahmad (Journal of agricultural, environmental and veterinary sciences, 2022)
This study aimed to determine how Palestinian farmers' attitudes toward raw wastewater (RWW) utilization. The study provided the socio- economic benefits, health, and environmental risks for reusing raw wastewater in crops irrigation. The survey of 100 farmers in the Wadi Al Far'a area, the sample selected randomly, revealed several significant knowledge gaps among RWW users., Farmers sometimes expressed contradictory views on the impact of irrigation from this source on the quality and quantity of the crop. However, they almost unanimously agreed on the value of wastewater as a source of providing fertilizers for the soil and that they had no choice because of the water scarcity. However, they were concerned about the harmful effects on their health and the environment. The regression study show, partial least squares route modeling with knowledge, proximity to wastewater canal, and value orientation were the most influential factors in determining perceived hazards of wastewater use. Consequently, results indicated that the farmers' awareness, ethical standard, communal unity, and willingness to continue planting statistically significantly impact their behaviors towards using RWW in irrigation. About 60% of the respondent farmers had a relatively moderate awareness about the quality of RWW and its adverse impacts on environmental aspects. In conclusion, some suggestions were made to increase the understanding of farmers which they not have other options from other water sources due to balance the harmful effects of raw wastewater with the potential economic benefits.
Keywords: Attitude; Raw wastewater irrigation; Awareness; Environment; Palestine